Pregnancy outcomes following hysteroscopic resection of uterine septum: does the size matter? a retrospective cohort study - Hadel Watad; Raanan Meyer; Michal Axelrod; Roy Mashiach; David Stockheim; Aya Mohr-Sasson (BMC Pregnancy and Childbirth)
Abstract Objective The benefits of surgical treatment of uterine septum malformation have recently been questioned. The aim of our study is to compare pregnancy outcomes following hysteroscopic resection of minor versus major septum. Methods A retrospective cohort study was conducted at a single tertiary university-affiliated medical center. All women who underwent hysteroscopic resection of uterine septum followed by a documented pregnancy between March 2010 to March 2019, were included. The septum size was assessed by ultrasound or during operative hysteroscopy by the surgeons. Two groups were defined based on septum size: 1. minor (< 50% uterine cavity); 2. major (≥ 50% uterine cavity). Cases with additional uterine malformations were excluded from the study. Data were compared between the groups before and following septum resection. A univariate and multivariate analyses were conducted. Results During the study period, 57 women met inclusion criteria, of these, 19 (33.3%) and 38 (66.7%) with minor and major septum, respectively. Baseline parameters were comparable between the groups. The rates of composite pregnancy complications before and following septum resection were also comparable between the two groups. Logistic regression analysis did not find septum size to be associated with pregnancy complications; however, comparing composite pregnancy complications prior and following septum resection revealed a trend of rate reduction in composite complications in the minor group (36.8% and 21.1% respectively) and a trend of increase in the major group (23.7% and 44.7% respectively). Conclusions Pregnancy outcomes following hysteroscopic resection of uterine septum were comparable between minor and major septum groups. Our results do not support septum removal to reduce pregnancy complications. However, due to the small sample size, further studies are required to strengthen our findings.